THE SUPERVISED STAGE AND THE PARTNER BETWEEN THE UNIVERSITY AND THE SCHOOL (Fiep Bulletin - online, 2014)
This work is from the first contacts of the author, teacher supervisor Supervised, mandatory course to a degree from a university in the city of Rio Grande / RS, as the school in which some trainees underwent pedagogical practice. Through the analysis of documents and resolutions that guide the practice internship in undergraduate courses, it was possible to realize the vision of this process from the looks of the school management team, composed of the direction, supervision and guidance school.
Keywords: Supervised; stage; teacher training; school.